What does research on child prodigies tell us about talent development and expertise acquisition? - Shavinina, L. V. (Talent Development & Excellence, 2010)
Research on child prodigies in general and the cognitive-developmental theory of the child prodigy phenomenon in particular shed light on the nature of talent development and expertise acquisition. According to the theory, this phenomenon is a result of an exceptionally accelerated mental development during sensitive periods that leads to the fast growth of a child`s cognitive resources and their construction into specific cognitive experience. This is how human expertise is acquired. The cognitive experience is a psychological basis of extraordinary intellectually creative achievements, which expresses itself in the prodigy`s unique intellectual picture of the world. The psychological nature of the prodigy phenomenon is thus formed by the sensitive periods - which explain prodigious development and talent development - and by cognitive experience, which explains prodigies` exceptional performance and achievements.